Handling behavior problems of children with special educational needs based on teacher analysis - Suparno Suparno; Hermanto Hermanto; Sukinah Sukinah; Wening Prabawati; Ade Putri Sarwendah; Galih Rasita Dewi; Dewi Barotuttaqiyah; Mumpuniarti Mumpuniarti (Intelektual Pustaka Media Utama, 2022)
Handling of behavior problems in children with special educational needs (CSEN) in the classroom is urgent for the classroom’s conducive atmosphere. Therefore, a review needs to be conducted to determine what steps the teacher may take for coping purposes in handling the behavior problems of CSEN, to determine the predictors for handling the behavior problems of CSEN, to identify the analysis basis for determining teacher predictors, and to figure out the effects of the behavior of CSEN based on the predictors chosen by the teacher. A survey was conducted on 109 teachers of CSEN. This research used a Google Forms questionnaire containing a list of statements to be chosen by teachers as instrument, and analysis was carried out by computing the frequencies at which the teachers chose the statements in percentage and by comparing teachers’ statements on the way they handled behaviors. The results show that the teachers were more inclined toward problem-focused coping (PFC), the predictor chosen was intimacy control, the teacher directed the children to do a task at the time a behaviour problem arose, and in choosing predictors, the teachers would rather calm the children down and give them comfort, making the children calmed.